Handbook of climate change impacts on river basin management : Technology,innovation, and management practices - Eslamian, Saeid (Boca Raton : CRC Press, 2024)
"Climate change is an alarming issue that has affected the globe at multiple levels. It involves not only rising temperatures but also changes to the original hydro-meteorological parameters of a region and the corresponding changes emerging in the various biotic or abiotic environmental features. Changing landscapes have become quite visible, and one of the prominent results of climate change has been the impact on the sediment yield and its transport. These changes have implications for various other environmental components, particularly soils, water bodies, water quality, land productivity, sedimentation processes, glacier dynamics, and risk management strategies to name a few. Understanding recent changes in sediment yield impacts due to changing climate will enhance the field of water resources management as well as land conservation techniques. This handbook examines hydrology, watershed, soil erosion, global climate change scenarios, changing dynamics of streamflow and erosion, impact of changing sediment dynamics, major problems associated with change in the original sediment balance in nature, the latest computing technologies incorporated in the studies, risk control and management measures. It also includes case studies from various countries, which will help illustrate the problem of climate change, as well as introducing region-specific approaches"--
Part I: Software Technologies; Part II: Management Practices; Part III: Recent Innovations
Includes bibliographical references and index.
Keywords: Watershed management. -- Software technologies; Watersheds -- Climatic factors. -- Recent inovations